Impact of Cambridge Curiculum Implementation on History Learning at SMA Fatih Bilingual School - Muhammad*, Devan; Umar, Mawardi; kamza, Muhjam (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the implementation of the Cambridge curriculum in history learning at SMA Fatih Bilingual School and the impact of the implementation of the Cambridge curriculum at SMA Fatih Bilingual School with the aim of describing how the implementation of the Cambridge curriculum on history learning at SMA Fatih Bilingual School and knowing the impact of the implementation of the Cambridge curriculum in the history learning process at SMA Fatih Bilingual School. This research uses qualitative methods with descriptive qualitative research techniques data collection using interviews and documentation for data analysis methods using Miles Huberman theory starting from data collection, data reduction, data presentation and conclusions and data condensation, data presentation and conclusion drawing. The results showed that the implementation of the Cambridge curriculum applied at SMA Fatih Bilingual School was not applied as a whole but several subjects that led to social science (Physics, chemistry, biology, mathematics, global perspectives and business studies). This is also applied based on the limited human resources available at SMA Fatih Bilingual School. The impact of the implementation of the Cambridge curriculum at SMA Fatih Bilingual School, student achievement has increased since the use of the Cambridge curriculum and on the learning side there are subjects that are not used including history because it is integrated into global perspective subjects. Based on the results of data analysis and discussion of research results, the conclusion that can be drawn is that the Cambridge curriculum is not fully implemented because it still combines with the national curriculum, but from the completeness it has met the school standards for implementing the Cambridge curriculum. The implementation of the Cambridge international curriculum at SMA Fatih Bilingual School has a positive impact on student learning achievement. However, on the contrary, it has a negative impact on history learning that is integrated into global learning perspectives as a result of the implementation of the Cambridge curriculum in schools so that students' knowledge of national history is reduced.